Design of universal multicoset sampling patterns for compressed sensing of multiband sparse signals - M. Elena Domínguez-Jiménez; Nuria González-Prelcic; Gonzalo Vázquez-Vilar; R. López-Valcarce (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2012)
Many problems in digital communications involve wideband radio signals. As the most recent example, the impressive advances in Cognitive Radio systems make even more necessary the development of sampling schemes for wideband radio signals with spectral holes. This is equivalent to considering a sparse multiband signal in the framework of Compressive Sampling theory. Starting from previous results on multicoset sampling and recent advances in compressive sampling, we analyze the matrix involved in the corresponding reconstruction equation and define a new method for the design of universal multicoset codes, that is, codes guaranteeing perfect reconstruction of the sparse multiband signal.